Hopelessness..? Turned Hopefullness..! – Salvaging A Molar with A Mother’s Touch– Case Report - Elangovan, Ramnath; Theyagarajan, Ramakrishnan; Dhas, Mejalla Muthiah Amala; Sekhar, Vidya (The Journal of Dentists, 2019)
Periodontitis is the inflammatory disease that leads to destruction of the supporting structures of the teeth. The early diagnosis and treatment of periodontitis is always not possible as the periodontitis progress with minimal or no pain. Regenerative medicine is the field that uses exogenous or endogenous stem cells for the regeneration of the lost periodontal tissues. This case report presents about salvaging a molar which was of poor prognosis and at the verge of extraction using Amniotic Membrane as a barrier membrane in the procedure of Guided Tissue Regeneration.